REKONSTRUKSI TARI JEPIN TALI DI KABUPATEN SINTANG - Sari, Anggi Wulan; Widyastutieningrum, Sri Rochana (Greget : Jurnal Kreativitas dan Studi Tari, 2022)
This research focuses on an in-depth analysis of the reconstruction process and outcomes of the Jepin Tali dance, reimagined by Anggi Wulan Sari in Sintang Regency. Jepin Tali is a traditional dance rooted in Malay culture, originating from Sintang, West Kalimantan. It is a key aspect of local heritage, performed in groups by both male and female dancers. The dance serves not only as entertainment but also as a vehicle for community education, promoting values such as cooperation and tolerance. The study adopts the reconstruction theory from the Burra Charter alongside the form theory introduced by Slamet. It employs a qualitative research approach with descriptive and interpretative methods. Data was collected through a combination of observation, literature review, and in-depth interviews with knowledgeable sources. The findings of the study are multifaceted. Firstly, the Jepin Tali dance acts as both a source of entertainment and a means of imparting social values. Secondly, the reconstruction process was structured around stages of exploration and organization, delving into the dance's historical and cultural significance. Thirdly, the reconstruction resulted in expanding the dance from three to sixteen movement variations, enriching the musical elements, makeup, costumes, and floor patterns. Fourthly, the dance is now performed by four female dancers, following a three-part structure—opening, main performance, and closing—using eight ropes as props. Lastly, the unique feature of the Jepin Tali dance lies in its use of ropes and the incorporation of the Siti Zubaidah chant, enhancing the artistic depth of the performance.